The relation of periodontal diseases to systemic diseases - Melanie Sadono Djamil; Boedi Oetomo Roeslan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
Background: The relationship between systemic disorders and periodontal disease has been studied extensively. With few exceptions, it is more accurate to consider systemic diseases to be contributing factors in the pathogenesis of periodontal disease rather than the primary etiologic factors. The development of periodontal disease cannot be separated from the weakening of immunologic and immunopathological responses. Periodontal disease may enhance susceptibility to certain systemic diseases in several ways. Lipopolysaccharide (LPS) and Gram-positive bacteria in the biofilm and proinflammatory cytokines produced from inflamed periodontal tissues may enter the circulation system causing the development of certain systemic diseases. On the other hand, through immunologic mediators, certain systemic disease may enhance susceptibility to periodontal disease caused by the decrease of immune responses and the increase of proinflammatory cytokines. Purpose: The Purpose of this article is to review the immunologic aspect of two way relationship between systemic diseases and periodontal diseases. Review: This review studied the relationship between general health status, systemic diseases, and periodontal diseases through immunopathological responses and the weakening of the immune system in the periodontal tissue. Conclusion: there is a two-way relationship between periodontal diseases and systemic diseases.